Plagiogyria longipinnata (Plagiogyriaceae), a new fern species from Mount Redondo, Dinagat Island, Philippines - Coritico, Fulgent P.; Orias, Pamela Joy F.; Acola, Mescel S.; Lagumbay, April Joie D.; Fritsch, Peter W.; Amoroso, Victor B. (Phytotaxa, 2026)
Plagiogyria longipinnata Coritico & Amoroso, a new species from Dinagat Island, Philippines, is formally described. This species is morphologically distinct from all other known members of the genus Plagiogyria by its consistently broadly lanceolate pinnae that are prominently long-stalked and entire. The discovery of P. longipinnata brings the total number of Plagiogyria species documented in the Philippines to eight. An updated key to the species of Plagiogyriaceae found in the Philippines is provided.